Impacts of ENERGY STAR Appliances on U.S. Multifamily Rents. (7th August 2020) - Hopkins, Erin A.; Carswell, Andrew T.; Love, Kim R.
Abstract : Implementation of ENERGY STAR appliances can be a significant source of energy efficiency within the multifamily rental industry. While there are many positive environmental outcomes by reducing energy consumption, there are also potential positive financial outcomes including lower operating costs, increased asset valuation, and higher rent potential. This study, through a rental hedonic estimation using the American Housing Survey (AHS) dataset, examines the rent impacts of ENERGY STAR appliances in multifamily rental units in the United States. The results suggest that there is a 1.6% average rent premium per ENERGY STAR product included in a rental unit. Knowing that these types of ENERGY STAR appliance changes may actually warrant rent increases could help improve the chances of changes taking place, but more research is needed with other datasets to further account for other rental unit features and location.